RfxCas13d-mediated inhibition of Circ1647 alleviates renal fibrosis via PI3K/AKT signaling pathway - Yufang Ni; Hongmin Zhang; Qianwen Xian; Wenjie Qin; Hongwei Su; Li Wang; Jianchun Li (Renal Failure)
Background Circular RNAs (CircRNAs) have been shown to be involved in the development of chronic kidney disease (CKD). This study aimed to investigate the role of Circ1647 in renal fibrosis, which is a hallmark of CKD.Methods In this study, we established a unilateral ureteral obstruction (UUO) model and delivered Circ1647 RfxCas13d knockdown plasmid into renal parenchymal cells via retrograde injection through the ureter followed by electroporation. After that, the pathological changes were determined by Hematoxylin and Eosin. Meanwhile, Immunohistochemistry, qRT-PCR and Western blot were conducted to assess the degree of fibrosis. In addition, overexpressing of Circ1647 in renal tubular epithelial cells (TCMK1) was performed to investigate the underlying mechanisms of Circ1647.Results Our results displayed that electroporation-mediated knockdown of Circ1647 by RfxCas13d knockdown plasmid significantly inhibited renal fibrosis in UUO mice as evidenced by reduced expression of fibronectin and α-SMA (alpha-smooth muscle actin). Conversely, overexpression of Circ1647 in TCMK1 cells promoted the fibrosis. In terms of mechanism, Circ1647 may mediate the PI3K/AKT Signaling Pathway as demonstrated by the balance of the phosphorylation of PI3K and AKT in vivo and the aggravated phosphorylation of PI3K and AKT in vitro. These observations were corroborated by the effects of the PI3K inhibitor LY294002, which mitigated fibrosis post Circ1647 overexpression.Conclusion Our study suggests that Circ1647 plays a significant role in renal fibrosis by mediating the PI3K/AKT signaling pathway. RfxCas13d-mediated inhibition of Circ1647 may serve as a therapeutic target for renal fibrosis in CKD.